1989
DOI: 10.1136/oem.46.7.479
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric concentrations of polycyclic aromatic hydrocarbons during chimney sweeping.

Abstract: Air sampled from the breathing zone of chimney sweeps during "dirty work" and soot samples were analysed for polycyclic aromatic hydrocarbons (PAH). A total of 20 PAH were quantified by gas chromatography-mass spectrometry in 115 air samples and 18 soot samples. These included benzo(b)fluoranthene, benzo(a)pyrene (BaP), chrysene, dibenz(a,h)anthracene, and indeno (1,2,3-cd)pyrene, all of which are animal carcinogens. The summed atmospheric concentration of these compounds depended on the type of fuel used and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…The organic part mainly consists of PAHs (Watson and Valberg 2001). Depending on the type of fuel used, several PAHs have been detected in the breathing zone of chimney sweeps during black-soot-sweeping in systems that use oil and solid fuel (Knecht et al 1989). Other studies have found high levels of inhalable combustion particulates (≥2.5 mg/m 3 ) (Gustavsson et al 2001) and dust (3–19 mg/m 3 ) (Andersson 1987) during chimney sweeping.…”
Section: Discussionmentioning
confidence: 99%
“…The organic part mainly consists of PAHs (Watson and Valberg 2001). Depending on the type of fuel used, several PAHs have been detected in the breathing zone of chimney sweeps during black-soot-sweeping in systems that use oil and solid fuel (Knecht et al 1989). Other studies have found high levels of inhalable combustion particulates (≥2.5 mg/m 3 ) (Gustavsson et al 2001) and dust (3–19 mg/m 3 ) (Andersson 1987) during chimney sweeping.…”
Section: Discussionmentioning
confidence: 99%
“…Chimney sweeps are primarily exposed to PAH from soot 10 , 12 , 13 , particularly during soot sweeping, the removal of soot from chimneys and boilers in private homes and industrial buildings that predominantly use wood, petroleum oil, and coal as fuel. Chimney sweeps can also be exposed to other hazardous substances from work such as arsenic, lead, nickel, asbestos, carbon particles, sulfur dioxide, carbon monoxide, detergents, and degreasing materials 10 , 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%
“…The exposure to 5 PAHs demonstrated to be carcinogenic in animals was about twice as high in soot from solid fuels as in soot from oil-fueled burners. 15 An extensive occupational hygiene survey performed in Sweden in 1985 and 1986 showed high dust levels during all work operations involving contact with soot. 13 Average levels of total dust during sweeping were 3, 9, 11, and 19 milligrams per cubic meter for the 4 most common sweeping operations, exceeding the Swedish threshold limit value of 3 milligrams per cubic meter for most work operations.…”
mentioning
confidence: 99%